Pengaruh Permainan Tebak Gambar Untuk Meningkatkan Pemahaman Kosa Kata Bahasa Arab Di Surabaya: Pengaruh Permainan Tebak Gambar Untuk Meningkatkan Pemahaman Kosa Kata Bahasa Arab Di Surabaya - Zuhrotul Mufidah; Moch Batdrus Soleh (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2022)
Arabic is one of the international languages ​​that is widely studied in Indonesia, especially at Madrasah Ibtidaiyah, Tsanawiyah, and Aliyah. Arabic is considered difficult because it has a vocabulary that changes a lot in every word form. Creative educators are able to provide a pleasant classroom atmosphere. The guessing game media is one of the innovations in the learning process to create a learning atmosphere that is not boring for students. The purpose of this study was to determine the effect of using picture guessing game media in improving understanding of Arabic vocabulary in Surabaya. After giving the pre-test, it was continued to give treatment (learning) and ended by giving a post-test to determine the effect of using picture-guessing game media to improve understanding of Arabic vocabulary in Surabaya. This study uses a quantitative method with the type of experimental class research which is intended to determine whether there is a consequence of